The two towers - Tolkien, J. R. R. (HarperCollins London, 2012)
Tolkien's invention of strange people, curious incidents, miraculous doings, is poured out into this second volume of his trilogy. As the story goes on the world of the Rings grows more vast and mysterious and crowded with curious figures